Letter (copy) : Goods for Spain - Tewson, Vincent
030-0123-001 Secretary's. HVT/FC/500. 6th July, 1938. Mr. Schevenels, The International Federation of Trade Unions, 9, Avenue D'Orsay, PARIS VIIe. Dear Mr. Schevenels, GOODS FOR SPAIN. I have to-day received word from the Co-operative Wholesale Society that the sandals and socks which I have referred to in previous correspondence are being despatched by the s.s. "C.W.S. Progress" from Garston to Rouen tomorrow, Thursday, the 7th instant. Probably you would notify Santiago of this fact. The consignment consists of 5,600 pairs of children's crepe rubber soled sandals and 300 dozen pairs of socks. From our conversation yesterday you will appreciate that the dried cod, dried milk, soap and the consignment referred to above are all being paid for by us out of the balance of the money at our disposal in the International Solidarity Fund. Yours sincerely, Assistant Secretary. 292/946/30/123